Flutuações posturais no equilíbrio estático : adaptações com a posição de perna única - Santos, Edenize Sodré dos (2013)
In this work, it was used statistical physics' technics to investigate standards in the postural fluctuations that characterize the static balance in human beings. Specifically, we analyze the behavior of the center-of-pressure (COP) velocity of 5 healthy subjects, in their regular position and on a single leg (right and left). We made use of a force platform to record the anteroposterior and mediolateral coordinates of COP. We investigated the temporal correlations in the velocity series, the velocity distribution and distribution of time intervals of return them. First, by making use of the Detrended Fluctuation Analysis (DFA) method, we verifed the velocity series show persistent behavior (H > 0; 5) for time intervals shorter than a certain value nc and anti-persistent behavior (H < 0; 5) for time intervals longer than nc. Next, we verified the velocity distribution shows a non-Gaussian behavior, being consistent with a q-Gaussian distribution with q > 1. Besides, we verified the distribution of time intervals of return shows a non-exponential behavior, well adjusted by a stretched exponential distribution. In each case we compared the relevant parameters' values for each position: regular, right and left leg. At last, we discussed the meaning of some main results.